Alpha-tomatine attenuation of in vivo growth of subcutaneous and orthotopic xenograft tumors of human prostate carcinoma Pc-3 cells is accompanied by inactivation of nuclear factor-kappa b signaling - Lee, S.T.; Wong, P.F.; He, H.; Hooper, J.D.; Mustafa, Mohd Rais (Public Library of Science, 2013)
Background: Nuclear factor-kappa B (NF-ÎºB) plays a role in prostate cancer and agents that suppress its activation may inhibit development or progression of this malignancy. Alpha (Î±)-tomatine is the major saponin present in tomato (Lycopersicon esculentum) and we have previously reported that it suppresses tumor necrosis factor-alpha (TNF-Î±)-induced nuclear translocation of nuclear factor-kappa B (NF-ÎºB) in androgen-independent prostate cancer PC-3 cells and also potently induces apoptosis of these cells. However, the precise mechanism by which Î±-tomatine suppresses NF-ÎºB nuclear translocation is yet to be elucidated and the anti-tumor activity of this agent in vivo has not been examined. Methodology/ Principal Findings : In the present study we show that suppression of NF-ÎºB activation by Î±-tomatine occurs through inhibition of I kappa B alpha (IÎºBÎ±) kinase activity, leading to sequential suppression of IÎºBÎ± phosphorylation, IÎºBÎ± degradation, NF-ÎºB/p65 phosphorylation, and NF-ÎºB p50/p65 nuclear translocation. Consistent with its ability to induce apoptosis, Î±-tomatine reduced TNF-Î± induced activation of the pro-survival mediator Akt and its inhibition of NF-ÎºB activation was accompanied by significant reduction in the expression of NF-ÎºB-dependent anti-apoptotic (c-IAP1, c-IAP2, Bcl-2, Bcl-xL, XIAP and survivin) proteins. We also evaluated the antitumor activity of Î±-tomatine against PC-3 cell tumors grown subcutaneously and orthotopically in mice. Our data indicate that intraperitoneal administration of Î±-tomatine significantly attenuates the growth of PC-3 cell tumors grown at both sites. Analysis of tumor material indicates that the tumor suppressing effects of Î±-tomatine were accompanied by increased apoptosis and lower proliferation of tumor cells as well as reduced nuclear translocation of the p50 and p65 components of NF-ÎºB. Conclusion/ Significance: Our study provides first evidence for in vivo antitumor efficacy of Î±-tomatine against the human androgen-independent prostate cancer. The potential usefulness of Î±-tomatine in prostate cancer prevention and therapy requires further investigation.